Wisata Alam Coban Putri Sebagai Objek Dalam Penguatan Ekonomi Masyarakat Desa Tlekung - Ananda Yumnatus Syafira; Elya Kurniawati; Nur Hadi (Mahesa Research Center, 2021)
Village community-based nature tourism is currently getting a lot of public attention. The government through its empowerment program also provides support to village communities when developing natural tourism in their area. The effectiveness of this empowerment program will later be able to improve the economy of rural communities sustainably. As is done in Coban Putri nature tourism, Tlekung Village, Junrejo District, Batu City. This research is qualitative, using a descriptive approach.While the sampling technique used is the purposive sampling technique, where informants are determined based on their role related to the development of natural tourism in Coban Putri. The purpose of this study was to determine how influential the Coban Putri natural tourism area is on the improvement of the economy of the Tlekung Village community after developing tourist attractions. The results obtained from this study indicate that the Coban Putri natural tourism area has sufficient influence on the economy of the Tlekung Village community, especially after development, so it is important for the government and the community to participate in developing Coban Putri natural tourism through empowerment programs so that it always has more appeal for tourists who visit.